Teachers' Strategies for Teaching Speaking Skills in Online Classes During the COVID-19 Pandemic - Venni Devita Mayor; Nurteteng; Rizqi Claudia Wardani H (TEKILA: Journal of Language Teaching and Literature, 2024)
This study examines the strategies used by teachers to teach speaking skills in online classes during the COVID-19 pandemic. A qualitative descriptive approach was used, with data collected through observations, interviews, and documentation. The findings show that teachers effectively used digital tools like WhatsApp, Zoom, and Google Meet to support speaking instruction. Key methods included conversation-based learning, such as role-playing and dialogue creation, and discussion-based strategies, like group debates. Teachers also provided regular feedback on live and recorded tasks to help students improve their speaking fluency and confidence. Despite challenges like limited internet access and varying digital skills, teachers adapted by simplifying tasks, offering flexible submission options, and maintaining communication. One significant finding is that using recorded dialogue submissions allowed students to practice at their own pace, reducing anxiety and improving participation. This study highlights how combining technology with student-focused teaching methods can overcome the limitations of online learning, offering practical insights for educators and policymakers to enhance speaking instruction in virtual classrooms.